Effect of 6 weeks high intensity interval training on selected factors of caadiac angiogenesis in rats with myocardial infarction. - Sara Karbalaiefar; Abbasali Gaieeni; Mohammadreza Kordi; Reza Nouri; Pedram Ghorbani (Shahid Beheshti University, 2020)
Purpose: Myocardial infarction (MI) is the irreversible cell death by ischemia in parts of myocardium. The molecular process of increased capillary density in response to activity and its appropriate intensity is not clear yet. Therefore, this research aimed to evaluate the effect of 6-week high intensity interval training on expressions of MMP-9, eNOS and the ratio of VEGF to COL-18 genes on rats with myocardial infarction. Methods: 12 Wistar male rats of 10 weeks old and mean weight 250-300gr were allocated to two groups of experimental (60 minutes of interval treadmill running for 4 minutes with the intensity of 85-90 percent of VO2max and 2 minutes of active rest at 50-60 percent of VO2max for 4 days a week for 6 weeks) and control group (without any training). Real-time PCR was used to assess the expression of MMP-9, eNOS VEGF and COL-18 genes after inducing MI, and shortening fractional and ejection fraction were investigated as echocardiographic indices. Data were analyzed in SPSS18 using independent t test (P≤ 0.05). Results: The findings showed that the amount of MMP-9 in HIIT (3.541 mg/ml) is significantly much more than the control group (1.002 mg/ml) (P=0.012) and the amount of eNOS in HIIT group (4.23 mg/ml) was also significantly much more than control group (3.68 mg/ml) (P=0.014) but there was no significant increase in the VEGF/COL-18 ratio in the HIIT group (1.856 mg/ml) as compared with the control group (1.245 mg/ml) (P=0.263). Conclusion: In general, 6 weeks of high intensity interval training can effectively increase MMP-9, eNOS and the ratio of VEGF to COL-18 genes and improve myocardial function in male Wistar rats after MI.